Rhinovirus as a rare cause of acute onset dilated cardiomyopathy due to myocarditis in a newborn: case report and review of the literature - Cebeci, Burcu; Oğuz, Demet; Ataoğlu, Emel; Elevli, Murat; Yolcu, Canan (The Turkish Journal of Pediatrics, 2022)
Background. Cardiomyopathies account for 1% of cardiac diseases that mainly originate from myocarditis in the form of dilated cardiomyopathy in the neonatal period. Viruses are the main cause of myocarditis resulting in dilated cardiomyopathy. Rhinovirus is the leading cause of viral respiratory infections though it is rarely severe. Case. We report a 17 day old newborn with acute onset dilated cardiomyopathy due to myocarditis that developed after a viral respiratory infection caused by Rhinovirus who was admitted to the emergency ward with shock due to heart failure and recovered without any complications. This is the first case reporting the causal role of rhinovirus and myocarditis in the neonatal period. Conclusions. A comprehensive approach is needed for the diagnosis of myocarditis in the case of unknown etiology and an extensive respiratory panel may be taken into consideration if there is a history or clinical symptoms of respiratory infection.
Keywords: dilated cardiomyopathy; myocarditis; newborn; rhinovirus